ANALISIS SWOT DALAM PENGEMBANGAN BISNIS JASA BENGKEL MOTOR - Harlindong, Dohan; Sutrisno, Agung; Monintja, Nita C.V. (Jurnal Tekno Mesin, 2024)
This research entitled "SWOT Analysis in Motorcycle Workshop Business Development" aims to provide a better understanding of business development strategies for motorcycle workshops, with a focus on the AHASS Utama Motor workshop in the East Langowan District, Minahasa. The SWOT analysis method is used to evaluate internal and external factors influencing the performance and position of the motorcycle workshop. The research findings identify internal factors such as strengths in providing comprehensive spare parts, strategic location, friendly and fast service, beginner mechanic training programs, genuine and quality spare parts, and weaknesses such as higher service prices, limited waiting room facilities, and insufficient product variety. External factors include opportunities such as increasing motorcycle maintenance needs, rising demand for two-wheeled vehicles, limited public transportation routes, as well as threats such as the emergence of counterfeit and reconditioned spare parts, and the emergence of many new competitors. From these findings, four main strategies are identified, namely S-O, W-O, S-T, and W-T, which include promotion, mechanic training, membership cards, product variety improvement, facility upgrades, technology utilization, genuine spare part education, service enhancement, discounts, and partnerships. It is hoped that these strategies will strengthen the competitiveness of AHASS Utama Motor motorcycle workshop in the market. Keywords: SWOT, Strategic Management, Motorcycle Workshop ABSTRAK Penelitian ini berjudul "Analisis SWOT Dalam Pengembangan Bisnis Jasa Bengkel Motor" bertujuan untuk memberikan pemahaman yang lebih baik tentang strategi pengembangan usaha bengkel motor, dengan fokus pada bengkel motor AHASS Utama Motor di Kecamatan Langowan Timur, Minahasa. Metode analisis SWOT digunakan untuk mengevaluasi faktor-faktor internal dan eksternal yang mempengaruhi kinerja dan posisi bengkel motor tersebut. Hasil penelitian mengidentifikasi faktor internal, seperti kekuatan dalam menyediakan sparepart yang lengkap, berada pada lokasi yang strategis, memiliki pelayanan ramah dan cepat, program pelatihan mekanik pemula, sparepart asli dan bermutu, dan kelemahan seperti harga layanan yang lebih tinggi, fasilitas ruang tunggu terbatas, dan varian jenis produk masih kurang. Faktor eksternal mencakup peluang seperti meningkatnya kebutuhan perawatan sepeda motor, peminat kendaraan roda dua yang semakin tinggi, Trayek angkutan umum yang terbatas, serta ancaman seperti munculnya isu spare part palsu dan rekondisi, muncul banyak pesaing-pesaing baru. Dari hasil tersebut, teridentifikasi 4 strategi utama, yaitu S-O, W-O, S-T, dan W-T, yang mencakup promosi, pelatihan mekanik, kartu keanggotaan, peningkatan variasi produk, perbaikan fasilitas, penggunaan teknologi, edukasi keaslian spare part, peningkatan layanan, diskon, dan menggandeng mitra. Harapannya, strategi-strategi ini dapat memperkuat daya saing bengkel motor AHASS Utama Motor di pasar. Kata kunci : SWOT, Manajement Strategi, Bengkel Motor